Strategy to Improve Graduate Competence Through UNIA Prenduan's Intensive Student Niha'ie Program in 2024 - Laeda Karima; Muru’atul Afifah (al-Afkar, Journal For Islamic Studies, 2026)
Principles and values in all aspects of academic activities and campus life. The main purpose of Islamic universities is to combine academic knowledge with strong Islamic values, so as to produce competent and highly moral graduates in accordance with the teachings of Islam. Therefore, some Islamic universities with the boarding schools basic have strategies to develop education to produce competent graduates for the sake of progress. In the context of Islamic universities based on boarding schools, UNIA Prenduan has one of its goals, namely to produce superior regeneration that is beneficial to society. This can prove that UNIA Prenduan is really trying to create a generation of graduates who are reliable and also competent. This study aims to determine the strategy of enhancing the competence graduates through the Intensive Niha’ie Program for Female Student at UNIA Prenduan Sumenep in Year 2024 and knowing the supporting and inhibiting factors in enhancing the competence through the Intensive Niha’ie Program for Female Student at UNIA Prenduan Sumenep in Year 2024. This research uses a qualitative approach with the type of case study. The data collection techniques used are interviews, observation and documentation. The subject of this research is the final semester intensive student of UNIA Prenduan, Kyai, and PO and PJ Niha’ie. Checking the validity of data in this study using Triangulation techniques and source triangulation. The results of this study indicate that the strategy of enhancing the competence graduates through the Intensive Niha’ie Program for Female Student at UNIA Prenduan Sumenep in Year 2024 is: Debriefing Niha’ie workshop, Muqabalah Syakhsiyyah, Dauroh Fikhiyyah and imamah practice, religious speech practice, Amaliyah tadries, Fathul kutub, Rihlah tarbawiyah tanazzuhiyyah. The supporting factors in the strategy of enhancing the competence graduates through the Intensive Niha’ie Program for Female Student at UNIA Prenduan Sumenep in Year 2024 are good cooperation between the person in charge of Niha’ie and female students, the enthusiasm of the students themselves in following each program, and support and direction from superiors and related parties. While inhibiting factors in the strategy of enhancing the competence of graduates through the Niha’ie program UNIA Prenduan Sumenep Year 2024, among others: the schedule of the Niha’ie program with the faculty program, time constraints, late disbursement of funds from BAUK.